Aluminum-based nanocomposites with hybrid reinforcements prepared by mechanical alloying and selective laser melting consolidation. Issue 18 (29th September 2015) - Ma, Chenglong; Gu, Dongdong; Dai, Donghua; Chen, Wenhua; Chang, Fei; Yuan, Pengpeng; Shen, Yifu
Abstract: Abstract : In this study, Aluminum-based nanocomposites with hybrid reinforcements were successfully prepared by mechanical alloying, followed by consolidation using selective laser melting (SLM). The evolution of particle morphology and microstructural features of the milled powders at various milling times was studied. The results indicated that the milled powder particles experienced a coarsening stage at the early 5 h milling and followed by a continuous refinement during 5–20 h milling. After 20 h of milling, the original coarse needle-like Al3.21 Si0.47 evolved into nanometer/submicrometer-sized spherical Al3.21 Si0.47 . Meanwhile, both fine Al3.21 Si0.47 and ex-situ nanoscale TiN particles distributed uniformly within the Al matrix. By SLM processing of the 20-h powder, a near fully dense part with a uniform microstructure consisting of circularly dispersed and submicrometer-sized reinforcement particles embedded in α-Al matrix was obtained. The Vickers hardness and coefficient of friction of the SLM-processed part reached 178 HV0.1 and 0.38, respectively.